RHEOLOGY AND GEODYNAMIC MODELLING: THE NEXT STEP FORWARD - Handy M.R.; Braun J.; Brown M.; Kukowski N.; Paterson M.S.; Schmid S.M.; Stöckhert B.; Stüwe K.; Thompson A.B.; Wosnitza E. (My University, 2001)
The application of continuum mechanics and microstructural analysis to geological studies over the past 30 years has spurred earth scientists to reassess fundamental tectonic processes such as subduction, collision and rifting in terms of dynamics. Armed with new analytical methods, geologists have returned to the field to look at rock structures with more mechanistic eyes. The advent of sophisticated computers, programs, and laboratory deformation equipment has facilitated the simulation of geodynamic processes that range in scale from the grain to the lithosphere. The result has been specialization, with the concomitant opening of communication gaps between geodynamicists, field geologists and rock mechanicists. Partly, these gaps reflect differences of perception and approach. In order to bridge these gaps, a workshop was organized after the DRM conference to debate how field and laboratory studies of deformed rocks can improve our understanding of lithospheric rheology, and in turn, how this understanding can be used to refine dynamic models of orogenesis. The workshop hosted participants with backgrounds in structural geology, experimental rock mechanics, metamorphic petrology and both numerical and analogue modelling. This paper summarizes the main controversies and conclusions reached during the workshop. For the sake of brevity, referencing in this summary is restricted to literature referred to during the oral presentations and to comments made by speakers themselves (names italicized).
Keywords: subduction; collision; rifting; lithosphere; rheology; orogenesis